The King and Ace Puzzle: A Proposal of Solution from a Term Logic - Miguel López-Astroga (Profil)
What I call the ‘king and ace puzzle’ here is an inference whose correct conclusion is hard to infer for people. There are reasoning theories offering explanations about this fact, including relevant frameworks such as the mental logic theory and the theory of mental models. In this paper, I claim that a term logic such as Inheritance Logic can also give us its account of that cognitive phenomenon. The key is the assumption of an equivalence: conditionals can be deemed as inheritance copulas.